Reviewing curriculum towards ASIIN international accreditation using analytical hierarchy process - Mulyanto, Angga Dwi; Suheriyanto, Dwi; Jannah, Akyunnul; Kusumadewi, Tarranita; Harini, Sri; Susanti, Elly (Bulletin of Applied Mathematics and Mathematics Education, 2023)
This research focuses on studying the curriculum of three study programs at the Faculty of Science and Technology, namely Biology, Informatics Engineering and Architectural Engineering. The purpose of this research is to see how ready the curriculum of the 3 study programs is to be submitted as ASIIN international accreditation material. The method used to measure curriculum readiness is using AHP. The results of this study are that from 3 study programs that have been assessed using AHP, the study program that is most ready for its curriculum is Informatics Engineering with a readiness of 73.4%, followed by Architectural Engineering, and after that Biology.